ANALISIS PRAKTIK ISTISHNA’ PADA PEMESANAN MAKANAN DI BAKERY AL-ZAYTUN INDRAMAYU DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH - Nurul Fitria, Laela; Syafi’i, Moch.; Maulana, Rizal (Cahaya Ilmu Bangsa, 2024)
This research examines the practice of istishna' when ordering food at Bakery Al-Zaytun Indramayu and from a sharia economic perspective on the practice of istishna' when ordering food at Bakery Al-Zaytun Indramayu. The first main problem of this research is the practice of istishna' when ordering food at Bakery Al-Zaytun Indramayu. The second main problem is, the perspective of sharia economic law on the analysis of istishna' practices in ordering food at Bakery Al-Zaytun Indramayu. The aim of this research is to determine the practice of istishna' in ordering food at Bakery Al-Zaytun Indramayu and the perspective of sharia economic law towards the analysis of the practice of istishna' in ordering food at Bakery Al-Zaytun Indramayu. This research method uses field research with a qualitative approach. The data collection procedures carried out were interviews, observation and documentation. The research results show that the Istishna' Agreement in practice at the Al-Zaytun bakery under the Al-Zaytun kitchen unit is based on a personal or special need. The ordering process follows standard operational procedures that have been initiated since its inception. In practice, this Istishna' contract uses a mechanism for paying the entire amount up front or in advance and with a letter of application that is known to the party concerned. Thus it can be concluded that this activity is an Istishna' contract. The application of the Istishna' agreement to ordering food at the Al-Zaytun Indramayu Bakery from a Sharia Economic Perspective can be concluded that it is in accordance with Sharia Economic Law. Keywords: Istishna', Selling Food Orders, Bakery Al-Zaytun;